2016
DOI: 10.1155/2016/7530942
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Reprogramming Using Defined Factors and MicroRNAs

Abstract: Development of human bodies, organs, and tissues contains numerous steps of cellular differentiation including an initial zygote, embryonic stem (ES) cells, three germ layers, and multiple expertized lineages of cells. Induced pluripotent stem (iPS) cells have been recently developed using defined reprogramming factors such as Nanog, Klf5, Oct3/4 (Pou5f1), Sox2, and Myc. This outstanding innovation is largely changing life science and medicine. Methods of direct reprogramming of cells into myocytes, neurons, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 101 publications
0
20
0
Order By: Relevance
“…Stem cells were first found in hematopoietic cells and thus designated hematopoietic stem cells (HSCs) [ 45 ]. Unequivocal proof of HSCs has given way to the prospective isolation of tissue-specific stem and progenitor cells [ 34 , 35 , 46 ]. Tumors may often originate from the transformation of normal stem cells, and cancer cells may include sub-populations of CSCs [ 28 , 30 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells were first found in hematopoietic cells and thus designated hematopoietic stem cells (HSCs) [ 45 ]. Unequivocal proof of HSCs has given way to the prospective isolation of tissue-specific stem and progenitor cells [ 34 , 35 , 46 ]. Tumors may often originate from the transformation of normal stem cells, and cancer cells may include sub-populations of CSCs [ 28 , 30 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that cancer cell aggregation led to formation of hypoxic tumoroids with robust secretion of EpCAM-exosomes and marked upregulation of reprogramming and stemness genes as increased CIC/CSC traits ( 2 ). A term of cellular “reprogramming” has been major after the development of induced pluripotent stem (iPS) cells ( 35 37 ) and more recently used in cancer studies as well ( 38 42 ). Intra-tumoral hypoxia, as well as a hypoxic milieu, can increase CIC/CSC properties through the hypoxia-inducible factor 1α (HIF-1α)-mediated induction of CIC/CSC genes, oncogenes, and ABC transporter genes ( 2 , 43 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are highly conserved ncRNAs that exert versatile biological functions. 28,29 Zhu et al indicated that LncRNA-ATB could promote viability, migration, and angiogenesis in human microvascular endothelial cells by sponging microRNA-195. 30 In addition, lncRNA-ATB could promote the progression of colorectal cancer by regulating miR-200c/CDK2 axis.…”
Section: Discussionmentioning
confidence: 99%